2009
DOI: 10.1111/j.1349-7006.2009.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

High expression of the evolutionarily conserved α/β hydrolase domain containing 6 (ABHD6) in Ewing tumors

Abstract: Despite improvements in the treatment of patients with Ewing family tumors (EFT), the prognosis for patients with advanced disease is still unsatisfactory. Recently, we identified lipase I as an EFT-associated gene that might be interesting for the development of new immunological or pharmacological treatment strategies. Lipase I is a member of the large protein superfamilies of alpha/beta hydrolases and serine hydrolases. In the present paper we describe high expression of another member of these superfamilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Recent evidence suggests that, like MAGL, ABHD6 can control the levels and signaling effi cacy of 2-AG in neurons ( 19,20 ). Overexpression of the two hydrolases has been found in certain types of cancer cells ( 12,18 ). However, in contrast to MAGL inhibition ( 12 ), knockdown of ABHD6 did not inhibit tumor cell growth ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that, like MAGL, ABHD6 can control the levels and signaling effi cacy of 2-AG in neurons ( 19,20 ). Overexpression of the two hydrolases has been found in certain types of cancer cells ( 12,18 ). However, in contrast to MAGL inhibition ( 12 ), knockdown of ABHD6 did not inhibit tumor cell growth ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…ABHD6 is a ‫ف‬ 30 kDa integral membrane protein with high expression reported in certain forms of tumors ( 17,18 ). Based on hydropathy analysis and biochemical studies, ABHD6 appears to be an integral membrane protein whose active site is predicted to face the cell interior ( 7 ).…”
Section: Activity-based Protein Profi Ling Of Serine Hydrolasesmentioning
confidence: 99%
“…Alpha-beta hydrolase containing 6 (ABHD6) is one of these genes. 59 In contrast to LIPI, ABHD6 seems to be regulated by EWSR1-ETS fusion proteins. 59,60 Nevertheless, TET-ETS negative tumors have also been shown to express ABHD6.…”
Section: Lipase H: a Second Lipase With High Expression In Ewing Tumorsmentioning
confidence: 99%
“…59 In contrast to LIPI, ABHD6 seems to be regulated by EWSR1-ETS fusion proteins. 59,60 Nevertheless, TET-ETS negative tumors have also been shown to express ABHD6. 5 Moreover, Epstein-Barr virus (EBV)-immortalized B-cells (so-called lymphoblastoid cell lines, LCL) express ABHD6.…”
Section: Lipase H: a Second Lipase With High Expression In Ewing Tumorsmentioning
confidence: 99%
“…Recent studies have shown that ABHD6 is highly expressed in several tumor cell lines, such as breast cancer cell line MCF7, but the significance of this high expression is not clear (Max et al, 2009). Another report demonstrated that inhibition of ABHD6 in brain produced the cannabnoid effect via accumulation of 2-AG, indicating the important roles of ABHD6 in regulating cell function (Marrs et al, 2010).…”
Section: Mag Lipasesmentioning
confidence: 99%